Reusable Flexible Concentric Electrodes Coated With a Conductive Graphene Ink for Electrotactile Stimulation - Stephens-Fripp, Benjamin; Sencadas, Vitor; Mutlu, Rahim; Alici, Gursel (Frontiers in Bioengineering and Biotechnology, 2018)
Electrotactile stimulation is a highly promising technique for providing sensory feedback information for prosthetics. To this aim, disposable electrodes which are predominantly used result in a high environmental and financial cost when used over a long period of time. In addition, disposable electrodes are limited in their size and configurations. This paper presents an alternative approach based on a 3D printed reusable flexible concentric electrode coated with a conductive graphene ink. Here, we have characterised the electrode and demonstrated its effective performance in electrotactile stimulation and sensory feedback for robotic prosthetic hands.